1956 at Ten and Beethoven’s Tenth: Edward Alexander and Hungary, 1965-66 - Glant, Tibor (Acta Neerlandica, 2020)
This article looks at Edward Alexander, an American diplomat who served in Hungary between 1965 and 1969, and his various writings. An Armenian-American man of letters, Alexander served in psychological warfare in World War II, then joined cold war radios and later the Foreign Service. Our focus is on the years 1965-67, when he served as Press and Cultural Affairs Officer at the Budapest Legation. Available sources include his official diplomatic reports, his rather large Hungarian state security file, a lifetime interview conducted under the aegis of the State Department in the late 1980s, a book on Armenian history, and a semi-autobiographical intelligence thriller he penned in 2000. These sources allow for a complex evaluation of his performance in Hungary and of his writing skills on account of his attempt to fictionalize his own exploits.